Yield determinants of a promising mungbean line under various planting densities - Rahman, Md Motior; Miah, A. Ahad (Universiti Putra Malaysia Press, 1995)
A field experiment was conducted during September to November, 1992 at the Regional Agricultural Reseach Station (RARS), Ishurdi, Bangladesh, to evaluate the growth performance of a mungbean line (cv. Mosk-I) under varying plant population densities. The treatments consisted of 20 x 10', 30 x 10', 40 x 10', 50 x 10', 60 x 10' and 70 x 10' plants ha-1. The lowest plant population density recorded the highest total dry matter (TDM) plant-1, crop growth rare (CGR), and pods plantl, while higher plant population (i.e. 50 or 60 plants m-2) produced the highest grain yield (> 1.30 t ha-1) and higher TDM per unit area. TDM, leaJ and pod dry matUir were positively correlated with grain yield. In contrast, stem and petiole dry matter showed negative correlation with grain yield.